Cognitive-semantic analysis of the meanings of words and phrases in English and Uzbek and their translation problems (Journal of Pedagogical Inventions and Practices, 2022)
This article deals with the cognitive-semantic analysis of the meanings of words and phrases in English and Uzbek and their translation problems, one of the most pressing problems of modern linguistics, the study of typology of languages, predicative analysis in English and Uzbek. The specificity of its compound is described in detail.